Try before you buy: Experimental evidence on willingness to pay for tailored extension advice in Nigeria - Oyakhilomen Oyinbo; Chamberlin, Jordan; Maertens, Miet (EiA, 2024)
Despite the recent advances in the development of digital decision support tools (DSTs) for agriculture and their potential in the transition of extension systems from general to tailored services, there is limited evidence of their widespread adoption in developing countries. Relatedly, there is growing concern about the long-term sustainability of digital advisory approaches, especially where extension systems face resource constraints. Using a randomized controlled trial and a choice experiment in Nigeria, we examine farmers’ preferences and willingness-to-pay (WTP) for a targeted digital decision support system that includes various tailored advice. We assess whether farmers’ WTP is influenced by a two-year free provision of DST-mediated site-specific nutrient management advice combined with information on investment returns. We find that farmers are willing to pay varying amounts of subscription fees to access different tailored advice, with the largest WTP value for climate advisory services. Results show that two years of exposure to experimentation and learning through DST interventions significantly increase farmers’ WTP for tailored advice, in particular for soil fertility management and market information. Our findings suggest that a fee-based digital extension model is a promising demand-driven approach that can enhance the upscaling of DSTs and support the financial sustainability of extension service providers.